SNP Detection in FREM2 Gene and Its Association with Carcass Quality in Bali Beef - Pertiwi, E. A.; Ulum, M. F.; Jakaria, J. (Faculty of Animal Science, IPB University, 2024)
The FRAS1-related extracellular matrix protein 2 (FREM2) gene is one of the genes that play a role in controlling marbling scores in beef cattle. This study aimed to identify SNPs in exon 6 of the FREM2 gene and its association with carcass quality in Bali beef using ultrasonography. A total of 93 cattle were used: 55 cattle from Banjarmasin slaughterhouse, South Kalimantan, Indonesia, 28 cattle from Bali Cattle Breeding Centre in Bali Province, and 10 cattle from UPTD Kupang Regency, NTT, Indonesia. SNP of the FREM2 gene was identified by using sequencing techniques and then genotyping by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The association of FREM2 gene SNPs with carcass characteristics was analyzed using the General Linear Model (GLM) method using SPSS software version 22. Carcass (longissimus dorsi thickness; back fat thickness) and meat (intramuscular fat; marbling score) characteristics were identified non-invasively using ultrasonography images and then analyzed with Image-J NIH software. SNP at position g.89327G>A was located in exon 6 of the FREM2 gene and did not change the amino acid (prolineproline) sequence in Bali beef. The genotyping results with PCR-RFLP technique SNP g.89327G>A FREM2|BccI gene has high diversity. The alleles of A and G were 0.747 and 0.253, respectively. The diversity of SNP g.89327G>A was significantly associated (p<0.05) with longissimus dorsi thickness (LD), while back fat thickness, intramuscular fat, and marbling score did not significantly different (p>0.05). Thus, SNP at position g.89327G>A in exon 6 of the FREM2 gene might be used as a candidate genetic marker for carcass quality in Bali beef.